The hope a novel - Wouk, Herman 1915-2019 (Little, Brown, 1993)
Through the lives of three military families, Wouk shows the wars and conflicts that have defined Israel's existence. Chronicles their lives from the 1948 War of Independence to the Six-Day War of 1967.
Keywords: Jewish families -- Fiction; Israel -- Fiction; Fiktionale Darstellung; Historical fiction; Jewish fiction; War stories